The Informal Employment – Factors and Public Policies for Its Limitation - Yaskal (Petrashchak), Oksana; Yaskal, Ihor; Kolosinska, Mariana; Бойда, Світлана (Икономически изследвания, 2021)
The purpose of this study is to outline the perspective public policies to limit informal employment. They are based on a study of its influential factors through The Doing Business international rating in the European Union and the EU candidate countries. For the group of “old” European countries, the priority measures are to improve the contracting procedures it terms of their numbers and time-consuming. For the group of new EU members, such measures are the reductions of the number of procedures to obtain electricity. For EU candidate countries, key steps to improve the regulation of informal employment include the raising legal awareness, reducing specific types of taxes and fees and increasing credit opportunities for business and people.
Keywords: informal economy; undeclared labor; factors that influence the informal employment rate; national employment policy; The Doing Business rating; International Labor Organization (ILO)